Deliberate rumination and posttraumatic growth: the mediating role of Christian gratitude and attachment to God - Vazquez, Veola E. (Mental health, religion & culture, 2022)
Using a community sample of 448 Christian adults with a history of trauma, the current study explored the mediating role of two religious variables, attachment to God and Christian gratitude, in the association between deliberate rumination and posttraumatic growth (PTG). Two parallel mediation analyses were conducted. In the first analysis, results revealed that anxious attachment to God mediated the association between deliberate rumination and PTG, but Christian gratitude did not. In the second analysis, neither avoidant attachment nor Christian gratitude mediated this same association. However, analyses revealed positive associations between PTG and Christian gratitude and anxious attachment to God. Post-hoc analysis revealed that intrusive rumination may better explain outcomes related to PTG when exploring these variables. Treatment implications, limitations, and directions for future research are presented.